THE ROLE OF MODERN METHODS IN THE STUDY OF LOWER SYRDARYA JETIASAR CULTURE AND SYSTEMIZATION OF MONUMENTS - Sobirov Alizoda (Scholars Digest Publishing, 2024)
In recent years, great attention has been paid to the development of tourism in our Republic. The issue of preservation of cultural heritage objects and their inclusion in the tourism system is on the agenda. In this regard, the work carried out in recent years at the monuments of Khorezm is noteworthy. On the example of the Ferghana Valley, similar exemplary works were undertaken in the city of Ahsikent.
Keywords: modern methods, monument, culture, development, modern education, historical researchers.